Quantitative Asset Pricing Implications of Endogenous Solvency Constraints - Alvarez, Fernando; Jermann, Urban J. (Review of Financial Studies, 2001)
We study the asset pricing implications of an economy where solvency constraints are endogenously determined to deter agents from defaulting while allowing as much risk sharing as possible. We solve analytically for efficient allocations and for the corresponding asset prices, portfolio holdings, and solvency constraints for a simple example. Then we calibrate a more general model to U.S. aggregate as well as idiosyncratic income processes. We find equity premia, risk premia for long-term bonds, and Sharpe ratios of magnitudes similar to the U.S. data for low risk aversion and a low time-discount factor.